STUDI FENOMENOLOGI PERSEPSI GURU DAN SISWA TERHADAP KULTUR BUDAYA SEKOLAH DI SDN 2 BRINGINSARI KABUPATEN KENDAL - Shofyan Abdul Gani; Husni Wakhyudin; Duwi Nuvitalia (CV. Denasya Smart Publisher, 2025)
The background to this research is the perceptions of teachers and students regarding the existing culture in SDN 2 Bringinsari that the culture there includes a very high level of caring and it could be said that the relationship between the people there is good. The aim of the research is to determine the perceptions of teachers and students regarding the culture at SDN 2 Bringinsari. This type of research is descriptive qualitative research with data collection through observation, questionnaires, interviews and documentation. The subjects of this research are teachers and students of SDN 2 Bringinsari. The research results were obtained from 10 statements written in the questionnaire as well as daily activities. It is hoped that the culture that is usually taught in learning can provide changes for the better, even if slowly..